Enzyme‐Free Unlabeled DNA Logic Circuits Based on Toehold‐Mediated Strand Displacement and Split G‐Quadruplex Enhanced Fluorescence. (28th February 2013) - Zhu, Jinbo; Zhang, Libing; Li, Tao; Dong, Shaojun; Wang, Erkang
<x xml:space="preserve">Abstract</x> Adopting fluorescence of PPIX enhanced by a split G‐quadruplex and toehold mediated strand displacement reaction, a series of unlabeled fluorescent logic gates is set up and some of them are cascaded into circuits. Controlled release of PPIX, which is also a photosensitizer in photodynamic diagnosis and therapy, is realized by this circuit, making it a wise choice for DNA computing. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>